Preparation and evaluation of polymeric carbamazepin spherical crystals by emulsion solvent diffusion technique - Yadav, Adhikrao V; Yadav, Venkat B (Asian Journal of Pharmaceutics (AJP), 2014)
In this study, a significant effect of different polymers on improving the solubility, dissolution rate, and physicochemical properties of carbamazepine (CBZ) has been demonstareted by emulsion solvent diffusion technique, with ethanol– chloroform–water as the solvent system. The hydrophilic polymers like polyethylene glycol, chitosan, and hydrophobic polymer Eudragit RSPO were used in the recrystallization process. The pure drug CBZ and the prepared spherical crystals of CBZ with different polymers were characterized in terms of morphology (microscopical photograph), X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), drug contents, solubility, dissolution rate, crushing strength, wettability, flowability, and packability. The FTIR spectra of the prepared spherical crystals showed that changes in the chemical nature occur and do not present great fingerprint difference. The XRD also revealed a characteristic decrease in crystallinity. The solubility and dissolution studies demonstrated a marked increase in solubility and dissolution rate in comparison with the pure drug. The prepared spherical crystals with different polymers exhibited excellent physicochemical properties like flowability, packability, and wettability compared with the pure drug. The spherical crystals with polyethylene glycol and chitosan showed higher crushing strength when compared with the hydrophobic polymer (Eudragit RSPO).